An Islamic Legal Review of Fixed-Tariff Fishing at Kasdi Fishing in Rano Village - Rini Indriyani; Nilfatri; Siti Fatimah; Kurniawan; Triyana Wulandari; Hasna Dewi (Zabags International Journal of Islamic Studies, 2025)
This study examines the practice of fixed-tariff recreational fishing at Kasdi Fishing in Rano Village from the perspective of Islamic law, focusing on the applicability of the ijarah contract and the prohibitions against gharar and maisir. The phenomenon where anglers pay an upfront fee without prior knowledge of catch outcomes raises questions about fairness and contractual certainty. The primary aims are to describe the tariff system in place and to assess its conformity with muamalah principles. A qualitative field approach was employed, using semi-structured interviews, direct observation, and documentation involving the owner, visitors, community leaders, and religious authorities. Findings indicate that the upfront fee functions as a payment for the right to use facilities and time (a service-oriented ujrah), rather than as a wager on catch results; the uncertainty inherent in possible zero catch is considered a normal, light degree of risk and does not amount to major gharar or to maisir when transactions are transparent and consented. The study contributes to contemporary fiqh muamalah by extending the practical application of ijarah to recreational fisheries and by offering a service-contract model that aligns commercial practice with Islamic contractual ethics.